Connecting the dots between breast cancer, obesity and alcohol consumption in middle-aged women: ecological and case control studies - E. R. Miller; C. Wilson; J. Chapman; I. Flight; A.-M. Nguyen; C. Fletcher; Ij Ramsey (BMC, 2018)
Abstract Background Breast cancer (BC) incidence in Australian women aged 45 to 64 years ('middle-aged') has tripled in the past 50 years, along with increasing alcohol consumption and obesity in middle-age women. Alcohol and obesity have been individually associated with BC but little is known about how these factors might interact. Chronic psychological stress has been associated with, but not causally linked to, BC. Here, alcohol could represent the 'missing link' - reflecting self-medication. Using an exploratory cross-sectional design, we investigated inter-correlations of alcohol intake and overweight/obesity and their association with BC incidence in middle-aged women. We also explored the role of stress and various lifestyle factors in these relationships. Methods We analysed population data on BC incidence, alcohol consumption, overweight/obesity, and psychological stress. A case control study was conducted using an online survey. Cases (n = 80) were diagnosed with BC and controls (n = 235) were women in the same age range with no BC history. Participants reported lifestyle data (including alcohol consumption, weight history) over consecutive 10-year life periods. Data were analysed using a range of bivariate and multivariate techniques including correlation matrices, multivariate binomial regressions and multilevel logistic regression. Results Ecological inter-correlations were found between BC and alcohol consumption and between BC and obesity but not between other variables in the matrix. Strong pairwise correlations were found between stress and alcohol and between stress and obesity. BMI tended to be higher in cases relative to controls across reported life history. Alcohol consumption was not associated with case-control status. Few correlations were found between lifestyle factors and stress, although smoking and alcohol consumption were correlated in some periods. Obesity occurring during the ages of 31 to 40 years emerged as an independent predictor of BC (OR 3.5 95% CI: 1.3-9.4). Conclusions This study provides ecological evidence correlating obesity and alcohol consumption with BC incidence. Case-control findings suggest lifetime BMI may be important with particular risk associated with obesity prior to 40 years of age. Stress was ecologically linked to alcohol and obesity but not to BC incidence and was differentially correlated with alcohol and smoking among cases and controls. Our findings support prevention efforts targeting weight in women below 40 years of age and, potentially, lifelong alcohol consumption to reduce BC risk in middle-aged women.